Guillain-Barre Syndrome linked to SARS-CoV-2 infection – meta-analysis and literature review - Siekierko, Nikola; Żołnierek, Maja; Kotusiewicz, Wiktoria; Lewandowski, Mateusz; Bienia, Grzegorz; Lubczyńska, Zuzanna; Popravko, Yevheniia; Świętochowski, Jakub (Journal of Education, Health and Sport, 2023)
Background The novel coronavirus disease-2019 (COVID-19), which is caused by Severe Acute Respiratory Distress Syndrome coronavirus 2 (SARS-CoV2), was originally detected in Wuhan, China in December 2019. In this meta-analysis and literature review, we compared and summarized the clinical presentation, cerebrospinal fluid (CSF) and electromyography (EMG) findings and outcomes in SARS-CoV-2 patients with Guillain-Barre Syndrome (GBS) and its variants. Methods We conducted a literature review in February 2023 searching for terms “Guillain-Barre Syndrome and COVID-19", “SARS neurology”, “COVID-19 complications”. We used PubMed and Google Scholar databases inquiring case reports or series of cases published between April 1, 2020, and September 14, 2023. Results Of the 52 GBS cases 61,5% (n=32) were male and 39,5% (n=20) were female. The mean age was 57 years old. A total of 75% (n=33) patients presented acute inflammatory demyelinating polyneuropathy (AIDP) variant, 6,8% (n=3) presented acute motor axonal neuropathy (AMAN) variant, 15,9% (n=7) presented acute motor-sensory axonal neuropathy (AMSAN) variant. A total of 85,7% (n=42) of patients were diagnosed with albuminocytological dissociation. During the hospitalization, a total of 30,8% (n=16) required mechanical ventilation. A total of 61,5% (n=32) of patients were treated with a 5-day regimen of intravenous immunoglobulin (IVIG) in dose 0.4 g/kg/day. There were 46,1% (n=24) complete recoveries from GBS, 32,7% (n=17) partial recoveries and 9,6% (n=5) of patients did not respond to treatment. A total of 11,5% (n=6) of patients died. Conclusion It is crucial to follow patients with COVID-19 and GBS over time to estimate properly the efficacy of treatment and evaluate the real percentage of recovery and complications.